Building a bridge between patients and transplant healthcare professionals – a descriptive study. (7th October 2021) - Jansen, Nichon; Maple, Hannah; Forsberg, Anna; Loud, Fiona; McColaugh, Lone; Murphy, Mark; Fuertes, Juan; Gallego, Daniel; Paredes, David
Summary: This article describes a pathway for collaboration between transplant healthcare professionals and organ recipients. Under the umbrella of the European Society for Organ Transplantation (ESOT) a joint initiative started from three Sections and Committees of ESOT: EDTCO (European Donation and Transplant Coordination Organisation), ETHAP (European Transplant Allied Healthcare Professionals) and ELPAT (Ethical, Legal and Psycho‐social Aspects of Transplantation). The formal 'kick‐off' of the Advisory Board Meeting of the European Transplant Patient Organisation (ETPO) was during the ESOT congress in 2019. The aim was to produce a series of statements to serve as a path to dialogue between patients and transplant professionals and to define the next steps towards giving a voice to the patient network. To include the patients' perspectives, two surveys have been performed. The results identified the unmet needs and lead to a proposal for future plans. Educational activities have since started leading to a patient learning workstream. All initiatives taken have one purpose: to include patients, give them a voice and build a foundation for collaboration between patients and transplant professionals. ESOT has created a platform for mutual understanding, learning and a collaborative partnership between ETPO and European donation and transplant professionals. Abstract : This paper describes a pathway for collaboration between transplant healthcare professionals and organ recipients. Through the creation of the European Transplant Patient Organisation (ETPO), ESOT has provided a platform for mutual understanding, learning and collaborative partnership between patients and European donation and transplant professionals.